971 Neonatology-Osteopathy (Ne-O) Study: RCT on the Effect of Osteopathic Manipulative Treatment on Los. (October 2012) - Accorsi, A; Lucci, C; Pizzolorusso, G; Tubaldi, L; Cerritelli, F; Perri, FP
Abstract : Background and Aims: The use of osteopathic manipulative treatment (OMT) in preterm infants has been documented and results from previous studies suggest the association between OMT and length of stay (LOS) reduction, as well as significant improvement in several clinical outcomes. The aim of the present study is to show the effect of OMT on LOS in a sample of premature infants. Methods: A double blinded randomized controlled trial was conducted on preterm newborns admitted in a single NICU between 2010–2011. N=51 subjects free of medical complications and with gestational age >28 and < 38 weeks were enrolled and randomized in two groups: study group (N=21) and control group (N=30). All subjects received routine pediatric care and OMT was performed to the study group for the entire period of hospitalization. Endpoints of the study included differences in LOS and daily weight gain. Results: Results showed a significant association between OMT and LOS reduction (mean difference between treated and control group: –1.787; 95% c.i. –3.555, –0.0015; p<0.05). OMT was not associated to any change in daily weight gain. Conclusions: The present study confirms that OMT could play an important role in the management of preterm infants hospitalization.